The Influence of Competence and Motivation on Employe Performance with Organizational Commitment as an Intervening Variable at PT Pegadaian (Persero) Jakarta - Juparna Purba; Bomer Pasaribu; Eddy Sanusi P Silitonga (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
This study aims to determine the partial influence of competence on employe performance, the partial influence of motivation on employe performance, the partial influence of organizational commitment on employe performance, the partial influence of competence on organizational commitment, the partial influence of motivation on organizational commitment, and to analyze the indirect influence of competence and motivation on employe performance thru organizational commitment. The research was conducted on employes at PT. Pegadaian (persero) Jakarta. The sampling technique used the census sample method with 65 employes. Data analysis was performed using path analysis. Based on the analysis and discussion, it can be concluded that competence (X1) has a significant influence on employe performance (Y), motivation (X2) has a significant influence on employe performance (Y), organizational commitment (Z) influences employe performance (Y), competence (X1) influences organizational commitment (Z), motivation influences organizational commitment (Z), and competence and motivation influence employe performance thru organizational commitment.